Aplikasi Virtual Tour 3D Pabrik PT. X - Utomo, Willy Nugraha; -, Liliana -; Gunadi, Kartika - (Jurnal Infra, 2014)
Company X is a reputable company that has more than 1000 people employees. One of the routines that performed by company X is orientation for new employees, and there is an event that invites them to visit the factory. The location of the main office and the factory is far, so this activity lacks time efficiency. This application aims to facilitate company X in conducting new employee orientation so that the location can be seen in the virtual world.The first thing in the process of making the application is visiting the factory to determine the shape and position of the object, so that the expected results are shown to resemble its original condition. 3d object and its texture are created using Blender application that can be imported into the made application. Collision feature aims to prevent users from penetrating the objects.The position, shape and location of objects contained in the application already resemble the original plant site. The main obstacle in making this application is the creation time, so the detailed map of the plant cannot be completed. The main building, the production building and the warehouse have been made, only small objects contained in the main building have not been contained.